USE OF COMPUTED TOMOGRAPHY-BASED NOMOGRAM IN ADULT AGE PATIENTS TO PREDICT SUCCESS RATES AFTER SHOCK WAVE LITHOTRIPSY FOR RENAL STONES: A SINGLE CENTER EXPERIENCE - Iqbal, Nadeem; Hasan, Aisha; Singh, Gurdeep; Hassan, Mohammad Haroon; Nazar, Ahsan; Khilan, Muhammad Haroon; Malik, Shahzeb Irfan; Khawaja, Muhammad Athar; Akhter, Saeed; Iqbal, Daud; et al. (Journal of Ayub Medical College Abbottabad, 2021)
Background: The Triple D score is a novel and easy to use nomogram to predict shock-wave lithotripsy (SWL) outcomes. It is based on Computed Tomography (CT scan) parameters including stone density, skin-to-stone distance, and stone volume. However, its use has not been validated much as studies are sparse regarding its use. Our aim was to validate and evaluate accuracy of the Triple D scoring system in predicting SWL success rates. Methods: It was a prospective study of 277 patients who had undergone SWL procedure for renal stones. They were evaluated by using non-contrast tomography, before undergoing SWL. CT scan-based parameters including distance of stone to skin (SSD), stone volume (SV), stone density was assessed. Computation of Cut off values was done with receiver operating characteristics analysis. Score was assigned on the basis of these cut-off values and success rate of SWL was determined. This score ranged from 0 (least favourable score) to 3 (most favourable score). Results: Stone-free status was attained in 160 patients (57.7%), and 117 (42.3%) patients were labelled to have failed the procedure. Differences between these two groups in terms of Stone volume, stone density and skin to stone distance were significant. Triple D scores of zero,1, 2, and 3 had stone-free rates of 3.6%, 52.56%, 53.3%, and 93.1% respectively (p-vaue<0.001). Conclusion: shock-wave lithotripsy outcomes can be predicted with use of Triple D score and hence, it’s externally corroborated. It may help urologist in appropriate patient selection and hence decision making and patient counselling.